1975
DOI: 10.1002/pssa.2210300239
|View full text |Cite
|
Sign up to set email alerts
|

Stimulated emission of mixed molecular crystals

Abstract: The fluorescence spectra of anthracene crystals doped with tetracene and perylene in wide range of pumping have been studied at 4.2 to 300 K. Starting from impurity concen‐1 trations of (0.5 to 1) × 1017 cm−3 a superlinear growth and narrowing of one or of severa fluorescence spectrum bands have been observed at pumping levels of 1020 to 1022 cm−2 s−1. The intensity of the amplified bands increases 102 to 103 times with an increase of pumping by a factor of 3 to 5 relative to the threshold. The stimulated emis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1977
1977
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…An interesting materials approach to avoid reabsorption by enlarging the apparent Stokes shift was already explored in the 1970s utilizing small molecule host crystals like fluorene or anthracene (Ac; see Scheme ), doped with appropriate chromophores like tetracene acting as acceptors for the originally created exciton . As demonstrated for doped nanocrystals of DSB, often molar doping ratios of 10 −3 are sufficient to induce transfer efficiencies of 90% and more, due to efficient thermally activated exciton diffusion in the crystals, allowing effective tuning of the emission color over a large spectral range with fluorescence quantum yields up to unity .…”
Section: Light Managementmentioning
confidence: 99%
“…An interesting materials approach to avoid reabsorption by enlarging the apparent Stokes shift was already explored in the 1970s utilizing small molecule host crystals like fluorene or anthracene (Ac; see Scheme ), doped with appropriate chromophores like tetracene acting as acceptors for the originally created exciton . As demonstrated for doped nanocrystals of DSB, often molar doping ratios of 10 −3 are sufficient to induce transfer efficiencies of 90% and more, due to efficient thermally activated exciton diffusion in the crystals, allowing effective tuning of the emission color over a large spectral range with fluorescence quantum yields up to unity .…”
Section: Light Managementmentioning
confidence: 99%
“…[16][17][18] Doped organic molecular crystals have received much attention since the 1970s and stimulated emissions in some systems were subsequently observed. 19,20 Doping has the advantage for tuning the emission color and decreasing the absorption loss via energy transfer. For white-emissive doped organic crystal growth, the host-guest system of two cyan-orange components or three blue-green-red components is usually considered.…”
Section: Introductionmentioning
confidence: 99%
“…Despite their potential advantages, dye‐doped organic solid‐state crystals have received significantly less attention than organic solid‐state thin films. However, dye‐doping and co‐crystallization of organic solid‐state crystals to enhance luminance properties have been attempted . Wang et al recently reported the PL characteristics of tetracene‐ and pentacene‐doped OPV crystals, while Li et al observed gain‐narrowed emission from a co‐crystal of perylene and 1,3,6,8‐tetramethyl‐pyrene .…”
mentioning
confidence: 99%